Studi Fenomenologi: Penilaian Membaca dalam Pembelajaran Bahasa Indonesia di Sekolah Menengah Atas Pekanbaru - Sukenti, Desi; Jamilin Tinambunan; Muhammad Mukhlis; Erlina (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
Reading assessment is a form of assessment activity carried out by educators in assessing students' reading. This study uses a phenomenological approach to explore teachers' experiences as participants in learning to read stories, read poetry and read descriptive texts in developing reading assessments. This study involved 15 Indonesian language teachers and conducted in-depth interviews about reading assessments in schools. The theories used in this research are Setiadi (2016), Abdul (2003), Tarigan (1994), Yunus (2012), Tampubolon (2015), Razak (2001), Nurhayati (2009), Djiwandono (2011), and the theory of Burhan Nurgiyantoro (2014). In-depth interview analysis in this study shows that the assessment of reading saga pays attention to the assessment of speech sounds, words, sentences, letters, language, readings, pays attention to reading pauses, sentence breaks, paragraph breaks, sentence content, letter content, punctuation marks, appreciates the content. In contrast, the construction of poetry reading assessment includes the assessment of diction sounds, sounds, letters, sentences, rhymes, rhythms, stanzas, the figure of speech, confidence, language style, appreciation. Descriptive text-based assessment is to assess the accuracy of diction (use of vocabulary, conjunctions between sentences, clarity of language sounds); the assessment of the accuracy of the sentence structure of the reading pays attention to 3 assessments, namely the arrangement of sentence patterns, stringing sentences and the form of sentences used; and assessing the spelling and writing used including the assessment of punctuation, use of capital letters. Educators can use this research recommendation on the construction of reading assessment in high school in the concept of reading assessment in schools.